2018
DOI: 10.1016/j.mod.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial permeability transition pore in sea urchin female gametes

Abstract: Mitochondrial permeability transition pore (MPTP) has been associated to calcium homeostasis and reactive oxygen species (ROS) generation in several cell types. While extensively investigated in somatic cells, there are few data regarding MPTP phenomenon in gametes. The aim of the present work was to investigate MPTP occurrence in sea urchin female gametes. The protonophores CCCP and FCCP, and the Ca ionophore ionomycin, were used as pore inductors. Pore opening was monitored by mitochondrial potential sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The mPTP activity mainly appeared as a property of mammalian and yeast mitochondria, where it was intensively investigated. However recently the mPTP was also reported in mussel [183], in sea urchin oocytes [184], in the nematode Caenorhabditis elegans [185], in plathelminths [186] and insects [187,188], while it is still controversial in crustaceans [189,190]. Indeed, it is not a "vertebrate invention" to rule cell fate, as initially thought [191].…”
Section: How the Atp Synthase/hydrolase Is Involved In The Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…The mPTP activity mainly appeared as a property of mammalian and yeast mitochondria, where it was intensively investigated. However recently the mPTP was also reported in mussel [183], in sea urchin oocytes [184], in the nematode Caenorhabditis elegans [185], in plathelminths [186] and insects [187,188], while it is still controversial in crustaceans [189,190]. Indeed, it is not a "vertebrate invention" to rule cell fate, as initially thought [191].…”
Section: How the Atp Synthase/hydrolase Is Involved In The Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…Though the most extensive investigations of mitochondrial pore function have been in mammalian and yeast mitochondria (Jung et al, 1997;Azzolin et al, 2010;Carraro et al, 2014;He et al, 2017aHe et al, , 2017b, mPTP activity has been observed in a wide range of organisms and cell types. These include sea urchin oocytes (Torrezan-Nitao et al, 2018), plants (Curtis and Wolpert, 2002), plathelminths (Song et al, 2016), nematodes (Liu et al, 2016), insects (Pan et al, 2016;Ren et al, 2017), crustaceans (Konràd et al, 2011;Konrád et al, 2012; though see, e.g., Menze et al, 2010), and birds (Vedernikov et al, 2015). The prevalence of the mPTP across lineages points to the fundamental nature of the physiological function of this complex (Azzolin et al, 2010;Uribe-Carvajal et al, 2011).…”
Section: It Takes Two: Dimerization In Mitochondrial Atpasesmentioning
confidence: 99%
“…Accordingly, the formation of the mPTP was only described in sea urchin gametes [19], hypothesized in the opistobranch mollusk Aplysia [20] and undetected in crustaceans [21]. Clues of pore forming properties of F1FO-ATPase dimers were found in model organisms, namely Drosophila and yeast [22].…”
Section: Introductionmentioning
confidence: 99%